Application of the Technological Pedagogical and Content Knowledge (TPACK) Approach Based on Higher Order Thinking Skills (HOTS) in Islamic Religious Education Learning at the Madrasah Aliyah Level - Nurlailli Hidayati; Siti Choiriyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Technological Pedagogical and Content Knowledge (TPACK) framework is not yet fully understood by educators in learning practice. TPACK is the knowledge needed so that Islamic Education teachers can use the right technology, which is based on the material content and pedagogic aspects. This study aims to determine the application of the teacher's Technological Pedagogical and Content Knowledge (TPACK) in the implementation of learning the Akidah Akhlak subject in class XI at Madrasah Aliyah. The research method used is qualitative with a descriptive approach. Data collection in this study was carried out using observation, interview and documentation techniques. The validity of the data was carried out by means of source triangulation and method triangulation techniques. The results showed that the application of TPACK in learning was able to use technological devices both non-digital and digital using laptops, LCDs and teachers were able to use powerpoint, youtube videos, and google classroom in making learning materials. Teachers are able to choose the right learning model so that students can obtain information and can also develop critical thinking skills, classroom management with technology is carried out by teachers effectively and efficiently in learning practices and is able to apply assessment of the learning process.